KARAKTERISTIK IBU, RIWAYAT ASI EKSKLUSIF DAN RIWAYAT PENYAKIT INFEKSI DENGAN KEJADIAN STUNTING PADA BALITA 12-59 BULAN DI WILAYAH KERJA PUSKESMAS SUKMAJAYA - Farahdilla Azmii, Firlia Ayu Arini (Medika Respati : Jurnal Ilmiah Kesehatan, 2018)
AbstractStunting Prevalence in Sukmajaya District was high enough that could affect brain development. Stunting caused by factors, such as mother's knowledge, mother's education, and family income, history of exclusive breastfeeding and history of infectious diseases. The purpose of this study was to analyze the incidence of stunting, maternal nutrition knowledge, maternal education, family income, history of exclusive breastfeeding and history of infectious diseases related to stunting incidence in infants aged 12-59 months in the working area of UPT Puskesmas Sukmajaya. The research design was using Cross Sectional. Number of respondents in this study were 106 mothers of infant, taken by clustered sampling method. The study was conducted from April to May 2017. Height of infant, mother's nutritional knowledge, mother's education, family income, history of exclusive breastfeeding, and history of infectious diseases were obtained through interviews using questionnaires. The result showed that there were a significant (p <0.05) between correlation mother's nutritional knowledge (p = 0.007), family income (p = 0.037), and history of infectious disease (p = 0.006) to stunting in infants aged 12-59 months. Where as maternal education (p = 0.148) and history of exclusive breastfeeding (p = 0.177) there is no correlation (p> 0.05) to stunting in infants 12-59 months. Maternal nutritional knowledge, family income, and history of infection had a significant relationship to stunting in infants 12-59 months. While the mother's education and breast feeding exclusively history is not related to stunting in infant under 12-59 months in the work area of Sukmajaya Community Health Center. Keywords: Characteristics of mother's, breastfeeding exclusively history, history of infectious diseases, Stunting.